Historical representation in the novel of the Ediwan Elisbarti - Bechlem, Mouna (Journal of Human Sciences, 2023)
The third millennium witnessed a remarkable return to the historical novel, in a dialogue of history and a reshaping of its events and personalities, and among the most important historical texts is the novel of the ediwan elisbarti, which returned to a sensitive period of national history in which the Ottoman rule overlapped with French colonialism, and the revolutions of the Algerians against it, which makes us wonder about How to represent all these categories in the fictional text, and did the historical fiction change the image of each category, or did the novel reproduce the images in their stereotypical form? The cultural reading of the novel makes us acknowledge that the novelist reproduced in many passages stereotypes about the European, while the novel was distinguished in portraying the marginalized, especially women, and the revolutionaries, among ordinary Algerians.